Long range ebook - Box, C. J. (Joe Pickett, 2020)
Don’t miss the JOE PICKETT series—now streaming on Paramount+ Wyoming game warden Joe Pickett must investigate an attempted murder—a crime committed from a confoundingly long distance—in this riveting novel from #1 New York Times bestselling author C.J. Box. When Joe Pickett is asked to join the rescue efforts for the victim of a startling grizzly attack, he reluctantly leaves his district behind. One survivor of the grizzly's rampage tells a bizarre story, but just as Joe begins to suspect the attack is not what it seems, he is brought home by an emergency on his own turf. Someone has targeted a prominent local judge, shooting at him from a seemingly impossible distance. While the judge was not hit, his wife is severely wounded, and it is up to Joe to find answers—and the shooter. The search for the would-be assassin becomes personal when Nate Romanowski and his young family are targeted by the mysterious shooter. Beset by threats both man-made and natural, the two men must go to great lengths to keep their loved ones safe. “Impressive precision and heart-gripping suspense....Good characters, an extra good story, and great scenes of life and death in the wilderness.”— New York Times Book Review